Optimal Labour Income Taxation: A Flexible Moral Hazard Approach - Kocherlakota, Narayana R (Review of Economic Studies, 2026)
Abstract This article reconsiders the question of optimal labour income taxes for the very rich in the context of a flexible moral hazard model. In this setting, risk is not exogenous. Rather, each agent can affect the probabilities of all possible income outcomes by allocating a fixed time endowment across a variety of distinct tasks. I prove that the optimal income tax rates on high-end earners and the optimal Pareto tail index of the pre-tax labour income distribution are both endogenously determined by agent preferences. In particular, a society with less risk-averse agents will find it optimal to impose a lower tax rate on the rich, even though its members’ choices give rise to a smaller Pareto right tail index. In contrast, this kind of negative co-movement between inequality and optimal tax rates is a suboptimal response in the classical Mirrlees (1971)–Diamond (1998)–Saez (2001) setup to changes in the exogenous distribution of skills.